Thermal treatment of starch slurry in Couette-Taylor flow apparatus - Hubacz Robert; Masuda Hayato; Horie Takafumi; Ohmura Naoto (Chemical and Process Engineering)
In this paper, thermal processing of starch slurry in a Couette-Taylor flow (CTF) apparatus was investigated. Gelatinized starch dispersion, after treatment in the CTF apparatus, was characterized using such parameters like starch granule diameters (or average diameter), starch granule swelling degree (quantifying the amount of water absorbed by starch granules) and concentration of dissolved starch. These parameters were affected mostly by the process temperature, although the impact of the axial flow or rotor rotation on them was also observed. Moreover, the analysis of results showed a relatively good correlation between these parameters, as well as, between those parameter and apparent viscosity of gelatinized starch dispersion. Meanwhile, the increase in the value of the apparent viscosity and in shear-tinning behaviour of dispersion was associated with the progress of starch processing in the CTF apparatus. Finally, the CTF apparatuses of different geometries were compared using numerical simulation of the process. The results of the simulation indicated that the apparatus scaling-up without increasing the width of the gap between cylinders results in higher mechanical energy consumption per unit of processed starch slurry.